MORPHO-FUNCTIONAL EVALUATION OF FLAPS IN FACIAL CARCINOMAS - Cătălin Constantin Ciocan Pendefunda; Mihai Liviu Ciofu; Cristian Ilie Drochioi; Andrei Nicolau; Oana Elena Ciurcanu; Andrada Doscas; Otilia Boisteanu; Victor Vlad Costan (Romanian Society of Oral Rehabilitation, 2020)
The face is a complex anatomical structure and reconstructive surgery to repair soft facial tissue defects is difficult and requires careful attention. When choosing the reconstruction method, it should be taken into consideration the general condition of the patient with the associated comorbidities that may affect the local vascularization or favour the appearance of complications and necrosis of the flap. The retrospective study included 68 patients with different types of carcinomas located on the facial skin. For aesthetic reasons, the key areas of the face must be known and respected, avoiding unnecessary distortion due to the chosen reconstruction technique. Postoperative scars can be optimally camouflaged at the boundary between the different aesthetic units, where the observer's eye expects a change of contour. The inconvenience of "moving" existing pre-carcinomatous lesions from the adjacent skin into the defect must be considered when designing a flap, but also the need to be as economical with the soft tissues as possible, in order to obtain a better aesthetic appearance.